Respon Penawaran Basil dan Permintaan Masukan Usahatani Padi: Suatu Pendugaan Ulang - Pasandaran, Effendi; Simatupang, Pantjar; Supriyati, Supriyati (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 1995)
AbstractPrevious studies on rice farming output supply and input demand functions inÂ Indonesia are considered not consistent anymore with present situation, and hence should be reestimated, because of two principle weaknesses: (1) hired tractor is not treated as a variable cost; (2) chemical fertilizers are not separated by their types. Reestimation is conducted using a quadratic profit flmction with crossprovincial-time series data 1986-1991. The analysis shows that TSP is a significant substitute for mea and complement with other chemical fertilizer. Human labor is substitutive with tractor and complementary with chemical fertilizers. As a whole, the findings are consistent with their theoretical expectation.